Evaluation and modeling of adhesion layer in shock-protection structure for MEMS accelerometer. (November 2016) - Yamane, Daisuke; Konishi, Toshifumi; Safu, Teruaki; Toshiyoshi, Hiroshi; Sone, Masato; Masu, Kazuya; Machida, Katsuyuki
Abstract: This paper presents evaluation and modeling of adhesion layer in shock-protection structure for a MEMS accelerometer fabricated by the multi-layer metal technology. The shock-protection structure is used to limit the proof-mass displacement at the input of excess acceleration. To clarify the mechanical characteristics of the shock-protection structure, we investigate the relationship between the input acceleration and the adhesion force on the adhesion layer in the multi-layer metal structure. For the multi-physics simulation, we propose an equivalent circuit model for a shock-protection module combined with the acceleration module. The adhesion force on the adhesion layer is examined by tensile tests in order to obtain the simulation parameters. The multi-physics simulation results are consistent with the measured capacitance-acceleration characteristics. The transient and capacitance-acceleration simulations at the input of high acceleration are also demonstrated to show the non-linear behavior of the shock-protection structure. Therefore, it is confirmed that the proposed module is useful for the multi-physics simulation to analyze the shock tolerance. Highlights: An equivalent circuit model of a shock-protection structure module is proposed. The module is implemented in a multi-physics simulation platform. Multi-physics simulation results are consistent with measurement data. Transient and C-G simulations with high input acceleration are demonstrated. The module is useful to analyze the shock tolerance of MEMS accelerometer.